An experimental study of the solubility and speciation of tantalum in fluoride-bearing aqueous solutions at elevated temperature. (15th January 2017) - Timofeev, A.; Migdisov, Art. A.; Williams-Jones, A.E.
Abstract: The solubility of Ta2 O5 (solid) and the speciation of tantalum in HF-bearing aqueous solutions have been determined at temperatures of 100–250 °C and vapour-saturated water pressure. Tantalum is transported as the species Ta(OH)5 0 at low HF concentration and pH ∼1–3. At higher HF concentration, tantalum mobility is controlled by the species TaF3 (OH)3 − and TaF5 0 ; the presence of TaF5 0 is only evident at ⩽150 °C. Equilibrium constants range from −17.4 ± 0.45 to −16.4 ± 0.12 for the formation of Ta(OH)5 0 from crystalline Ta2 O5 and from −8.24 ± 0.64 to −8.55 ± 0.68 for the formation of TaF3 (OH)3 − at 100 and 250 °C, respectively. For TaF5 0, they were determined to be 0.13 at 100 °C and −0.35 at 150 °C. In many respects, the behaviour of tantalum in acidic fluoride-bearing solutions is similar to that of niobium. The solubility of Ta2 O5 (solid) is not dependent on HF concentration in fluoride-poor fluids, but rises rapidly at higher HF concentration. However, at the conditions of our experiments, namely a pH of ∼2, temperature up to 250 °C, and a wide range of HF concentrations, Ta2 O5 (solid) solubility is almost invariably lower than that of Nb2 O5 (solid). Modelling of Nb and Ta leaching confirmed the preferential mobility of niobium under most conditions expected in natural fluoride-rich hydrothermal systems. This modelling also demonstrated that both niobium and tantalum are rapidly deposited upon removal of fluoride from an acidic brine. As a result of hydrothermal alteration, the Nb/Ta ratios of secondary minerals may increase relative to those of the primary mineral, or remain largely unaffected, depending on the pH of the fluid.